(untitled) (Economic and Political Thought, 2014)
The article presents modern concepts of economics – sharing economy also called collaborative economy. According to the new principle, access is a new form of ownership – access to goods and services is becoming a new form of ownership. We no longer have to be owners of goods or services in order to use them as a consumer or an end user. In connection with the development of the Internet throughout the world, thousands of companies have been created that base their business model on sharing economy. There are more and more goods and services all over the world, which you do not need to own, but you can still use them and benefit from using these things. There is no doubt that this new global movement changes the way in which future economy will work. This paper provides an analysis of the current global trend of sharing economy on the basis of the results of a survey conducted by the agency Havas Worldwide in partnership with Market Probe International. 10 574 people aged over 16, representing 29 markets took part in the survey. Sharing economy is currently a very broad term, which covers not only sharing bicycles, cars and houses, but also common activities such as cooking. This new concept is growing rapidly across the world, so we should try to analyse how these companies operate and how they will work in the future. The author of the article tries to predict and describe possible trends in the development of sharing economy in the future and possible risks associated with it.